The effect of differences in work and rest ratios in high intensity interval training on physical performance - Angga Indra Kusuma; I Gede Dharma Utamayasa (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Training is something that athletes need to improve their physical performance. This study aims to examine the differences in the effects of HIIT training with different work and rest ratios on the physical condition of male badminton athletes at university level. The method applied in this study is an experimental method with a matching only design. The sample of this study was 30 male badminton players at university level. The number of samples used was the total number of athletes at the university. The results obtained were that training with a work and rest ratio of 1:1 can have a significant effect on physical condition. In addition, the ratio of 1:2 and 1:3 also has a significant effect on the physical condition of athletes. The conclusion in this study is that there is a difference in the effect between training with a ratio of 1:1, 1:2 and a ratio of 1:3 in improving physical condition, where the ratio of 1:1 has a better effect as one of the options as a training model in preparation before the match